Catholic school leadership : an invitation to lead - Hunt, Thomas C., 1930-2014; Oldenski, Thomas; Wallace, Theodore J. (Theodore Joseph), 1954- (Falmer Press, 2000)
Catholic School Leadership addresses many of the challenges facing those who prepare faith leaders and education leaders for the Catholic schools of the future. The well-known editors and contributors to this volume have written about their personal experiences with Catholic schools; the educational foundations of Catholic schools; teacher preparation and development; Catholic school leadership; dealing with parents and families; and the challenges of technology for Catholic schools. The contributions emphasize the perspectives of both scholars and practitioners within Catholic edu.